The Gospel of Matthew: worship in the Kingdom of Heaven - Heil, John Paul (Wipf and Stock Publishers, 2017)
The Gospel of Matthew encourages and inspires its audience to practice the true, authentic, and holistic worship required for believers in Jesus to live in the kingdom of heaven. In accordance with all that Jesus taught and exemplified regarding authentic worship, believers are invited to complement their worship of God by worshiping and praying to Jesus as God's beloved Son, who represents "God with us." They are also invited to complement their ritualistic worship, especially the baptism and Eucharist instituted for them by Jesus, with an ethical worship that extends to others, especially to disciples, children, and "the least ones" with whom Jesus identifies himself, the mercy God desires for a holistic worship. Indeed, a compassionate mercy toward all is the distinctive and noteworthy hallmark that characterizes the theme of worship in the kingdom of heaven, according to the Gospel of Matthew